Antenna coupled metamaterial inspired passive sensors for glaucoma monitoring - Çalıkoğlu, Ümmühan Aybüke. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Glaucoma is an eye disease that may cause blindness by damaging the optic nerve due to elevation of the intraocular pressure. In this thesis, a passive metamaterial inspired resonator sensor for non-invasive and continuous monitoring of glaucoma is developed to improve diagnosis accuracy and treatment of glaucoma. The geometry of the resonator is optimized such that it can be embedded in a conventional contact lens. The sensor is fabricated and embedded in a contact lens to be used for continuous glaucoma monitoring. Finite-element based models are developed to analyse the operation of the devices and to optimize the sensor structure. For this purpose, the contact lens placed on the eye model is examined by the nite element method and the displacement of the contact lens due to the increase in intraocular pressure is analyzed. Mechanical simulations are also given to examine the fabrication of the sensors. The proposed sensor is excited and interrogated using a tunable antenna. The resonant frequency of the resonator is measured by measuring the re ection characteristics with designed antenna which is tuned to be coupled to the resonator sensor. Theoretical and simulation based analysis for tunable antennas are also shown. In-vitro characterization of the antenna coupled contact lens sensor with respect to varying intraocular pressure levels of mechanical eye model are done experimentally. According to the results obtained, the sensitivity of the device, i.e. the change in resonant frequency for a unit change in pressure, is calculated as {u100000}31:09 kHz=mmHg with the resolution of 1:98mmHg. The experimental results supported by nite-element based models indicate that the demonstrated device is suitable for glaucoma diagnosis and monitoring.
Keywords: Glaucoma.